مفهوم المواطنة وأبعادها في فكر مالك بن نبي - بوفولة, مراد; بن صويلح, ليليا (جامعة الوادي - University of Eloued, 2021)
تركز هذه الورقة على بحث مفهوم المواطنة عند مالك بن نبي وموقفه النظري إزاء منحى استيراد المنتوج الفكري والبناء المعرفي من بيئة مجتمعية غربية بتوجهاتها الايديولوجية ومعتقداتها الوجودية إلى بيئة عربية بمرتكزات ايمانية ومنظومة قيمية تمتثل سلطة الضمير الجمعي فتنفرد مشهد المغايرة عن سابقتها وتلتزم منطق الخصوصية في مسارها التطوري. وقد تم توظيف المنهج المقارن، بطريقة استقرائية للتوصل لمعرفة الموقف الذي أتخذه مالك بن نبي من الحضارة الغربية، حيث تجلى رفضه لمختلف صور الاسقاطيه الفكرية، لاختلاف الخصوصيات السوسيو ثقافية بين مجتمع البيئة العربية المسلمة والمجتمع الغربي، إذ يرى بأن الانطلاقة الحضارية تكون ببناء وعي المواطن وبث فيه روح الحيوية، فيتحول من فرد إلى شخص، أومن فرد خام إلى فرد مكيّف قادر على الاندماج الاجتماعي مع بيئتة. خلصت الدراسة في أبعادها التحليلية لمقاربة المشروع الفكري لمالك بن نبي إلى فكرة جوهرية مفادها أن السلوك الحضاري في فكر مالك بن نبي دلالة ضمنية قوية في ابعادها لفكرة المواطنة كإشارة دالة عن ثقافة العيش المشترك، في مجتمع تربط أفراده شبكة علاقات اجتماعية، تنسج مع ديناميكية أعضائه، في إطار تفعيل الأفكار النابعة من مرجعية دينية، وبثقافة محلية ناتجة عن تفاعل العوالم الثلاثة عالم الأفكار، عالم الأشخاص وعالم الأشياء. Abstract: The present paper focuses on examining the concept of citizenship of Malik Ben Nabi and his theoretical attitude towards the import of intellectual output and knowledge-building from a Western community environment with its ideological orientation and existential beliefs to an Arab environment with faith-based and value-based systems that comply with the authority of the collective conscience. The comparative approach was used, in an experimental way, to find out about Malik Ben Nabi's position on Western civilization. His rejection of various forms of intellectual projection was reflected in the different cultural characteristics of the Arab Muslim environment and Western society. In its analytical aspects of the approach to Malik Ben Nabi's intellectual project, the study found the fundamental idea that the civilizational behavior of Malik Ben Nabi is strongly implicit in its dimensions of the notion of citizenship as a reference to the culture of shared living, in a society whose members have a social relations network, which weaves with the dynamics of its members, in the context of the activation of ideas emanating from religious reference, and in a local culture resulting from the interaction of the three worlof ideas, the world of people and the world of things.
The concept of citizenship and its dimensions in the thinking of Malik Ben Nab
مقال
Keywords: مواطنة، ثقافة، حضارة، دين، أفكار; citizenship , civization, culture, religion, ideas